2021
DOI: 10.19182/remvt.36801
|View full text |Cite
|
Sign up to set email alerts
|

Variations saisonnières des performances de reproduction des brebis Ouled Djellal dans la région de Chlef, Algérie

Abstract: La reproduction contribue directement à la rentabilité des élevages et les performances associées sont synthétisées dans des indicateurs économiques centraux dans l’analyse des performances globales des systèmes d’élevages. L’activité sexuelle et ainsi les performances reproductives des brebis sont affectées par des facteurs environnementaux, en premier lieu la photopériode. La brebis Ouled Djellal, naturellement davantage désaisonnée que d’autres races ovines, est peu sensible au facteur photopériodique, parv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…The total fertility rate in this study was lower compared to that of (Chellig 1992) in a similar sheep breed (100%), with a difference of 22% compared to our results and the rates recorded in Ouled Djellal breed described by (Dekhili, 2004) in Setif region, where the average was 92% and those of (Arbouche et al 2013) which was 88% with a difference of 14% and 10% respectively.Our findings are consistent with the 75% fertility rate reported by (Zidane et al 2021) in the Ouled Djellal sheep breed in the Chlef region of the semi-arid western Algerian Highlands. On the other hand, (Mefti Korteby et al 2017) reported a fertility rate of 83% with a difference of 5%.…”
Section: Fertilitysupporting
confidence: 92%
“…The total fertility rate in this study was lower compared to that of (Chellig 1992) in a similar sheep breed (100%), with a difference of 22% compared to our results and the rates recorded in Ouled Djellal breed described by (Dekhili, 2004) in Setif region, where the average was 92% and those of (Arbouche et al 2013) which was 88% with a difference of 14% and 10% respectively.Our findings are consistent with the 75% fertility rate reported by (Zidane et al 2021) in the Ouled Djellal sheep breed in the Chlef region of the semi-arid western Algerian Highlands. On the other hand, (Mefti Korteby et al 2017) reported a fertility rate of 83% with a difference of 5%.…”
Section: Fertilitysupporting
confidence: 92%
“…The average fertility rate of 78,8% observed for the Hamra breed was overall low compared with that obtained in our study for the Rumbi breed with 87,14%. According to (Zidane et al, 2021), the maximum fertility rate observed in the Ouled Djellal breed of 88% is similar to that of the Rumbi breed. Moreover, these rates obtained remain far from the reproduction objectives in sheep farms which are 95% (Heinrichs and Radostits, 2001).…”
Section: Discussionmentioning
confidence: 70%
“…In different production systems, breeding profitability expressed by productivity is a major concern of sheep farming worldwide (Belhadia et al, 2020;Zidane et al, 2021). Its improvement constitutes an important objective for the ovine meat production industry.…”
Section: Introductionmentioning
confidence: 99%